ANALISIS ETIKA BISNIS ISLAM TERHADAP PERILAKU PEDAGANG KAKI LIMA DI PASAR SAGUMPAL BONANG PADANGSIDEMPUAN - Nasution, Ahmad Ridwan; Taufiq, Muhammad (Lembaga Pengembangan Kinerja Dosen, 2023)
Business ethics is a set of norms that are binding on every economic actor and must be owned by every trader because it is a recommendation from the Islamic religion. This study aims to determine whether the behavior of street vendors at the Sagumpal Bonang Padangsidempuan market is in accordance with Islamic business ethics. This type of research is field research using qualitative descriptive analysis methods. Based on the results of observations and interviews conducted by researchers with several traders, it can be concluded that traders do not know about Islamic business ethics. However, in terms of its implementation, it has applied rules that are justified in Islamic teachings, including the principle of monotheism, the principle of balance/justice, the principle of free will, the principle of responsibility, and the principle of honesty. In this study it was also found that traders had applied the values ​​of good behavior in life by applying the characteristics of the Prophet Muhammad, namely siddiq, amanah, tabligh, and fathanah.